The perception of your body by homosexual people. Eating disorders - Kołodziej, Kosma; Urtnowska-Joppek, Katarzyna; Suwała, Karolina (Journal of Education, Health and Sport, 2018)
Introduction Problems related to eating disorders such as anorexia, bulimia and obesity turns out to be very common in the LGBT group. The paper presents a review of research in this field showing the relationship between the influence of the environment, homophobia and lack of tolerance to the problem presented in the topic and a scale of this problem occurring in the presented minority group. Aim The aim of the work is to draw attention to the scale of the problem and the specificity of the LGBT group in the field of eating disorders. Presenting factors which are a predisposition to such disorders, may be useful to medical staff, psychologists, educators and therapists dealing with the problem of eating disorders. Another aim is to create a scientific publication on the topic of sexual minorities, which is still lacking in comparison with foreign magazines in our country. Brief description of the state of knowledge LGBT group turns out to be a group with an increased risk of eating disorders. Gays are a group exposed to anorexia and bulimia. However, the group of lesbians has been defined with an increased risk of overweight and obesity. According to a review of contemporary research in this area, the problems related to nutrition are influenced by homophobia, lack of social acceptance, heterosexual and episodes of sexual abuse in childhood. Conclusions There is a huge need of knowledge for specialists dealing with eating disorders about the specificity of the LGBT group. Their greater competences can positively influence the prevalence of eating disorders in this group and positively influence the course of treatment of such people.